AUTOFLUORESCENCE AND AXIAL LENGTH AS PROGNOSTIC FACTORS FOR OUTCOMES OF MACULAR HOLE RETINAL DETACHMENT SURGERY IN HIGH MYOPIA. Issue 3 (March 2015) - Arias, Luis; Caminal, Jose M.; Rubio, Marcos J.; Cobos, Estefania; Garcia-Bru, Pere; Filloy, Alejandro; Padron, Noel; Mejia, Karol
Abstract : Purpose: To evaluate the results of fundus autofluorescence and axial length as prognostic factors for surgical outcome of macular hole retinal detachment in high myopic patients. Methods: This is a retrospective, interventional, nonrandomized study. Patients were treated with posterior vitrectomy, internal limiting membrane peeling, and silicone oil tamponade. Best-corrected visual acuity, axial length, fundus autofluorescence, and spectral domain optical coherence tomography images were obtained. Results: Fifteen eyes from 15 patients (mean age, 69.4 years) were evaluated. The mean refractive error was −19 diopters, and the mean axial length was 29.9 mm. The mean best-corrected visual acuity (logMAR) improved from 2.17 to 1.42 ( P = 0.02) after a mean follow-up of 19.3 months. Spectral domain optical coherence tomography scans showed retinal detachment resolution in 13 eyes (86.6%) and macular hole closure in 9 eyes (60%). Fundus autofluorescence showed macular hypoautofluorescence with foveal involvement (mean area of 9.7 mm 2 ) in 10 eyes (66.6%). Postoperative best-corrected visual acuity was significantly worse in these eyes ( P = 0.009). Axial length >30 mm was found in the 2 cases with recurrent retinal detachment and in 4 of the 6 cases without macular hole closure (66.6%). Conclusion: Macular hole retinal detachment in high myopic patients can be successfully treated with vitrectomy, internal limiting membrane peeling, and silicone oil. Axial length >30 mm and macular hypoautofluorescence with foveal involvement seem to be prognostic factors for a worse anatomical and visual outcome. Abstract : Axial length >30 mm and macular hypoautofluorescence with foveal involvement seem to be prognostic factors for a worse anatomical and visual outcome in highly myopic patients with macular hole retinal detachment.